Предмет: Математика,
автор: darag6179
96(х-1)-(7х-64)=38(2-х)+3(17+2х)+83=?
Ответы
Автор ответа:
1
96(х-1)-(7х-64) = 96x - 96 - 7x + 64 = 89x - 32
38(2-х)+3(17+2х)+83 = 76 - 38x + 51 + 6x + 83 = 210 - 32x
===================== а если это уравнение то =====================
96(х-1)-(7х-64)=38(2-х)+3(17+2х)+83
96x - 96 - 7x + 64 = 76 - 38x + 51 + 6x + 83
89x - 32 = 210 - 32x
89x + 32x = 210 + 32
121x = 242
x = 242 : 121
x = 2
38(2-х)+3(17+2х)+83 = 76 - 38x + 51 + 6x + 83 = 210 - 32x
===================== а если это уравнение то =====================
96(х-1)-(7х-64)=38(2-х)+3(17+2х)+83
96x - 96 - 7x + 64 = 76 - 38x + 51 + 6x + 83
89x - 32 = 210 - 32x
89x + 32x = 210 + 32
121x = 242
x = 242 : 121
x = 2
Автор ответа:
0
Начинаем решать уравнение :
96x - 96 - 7x + 64 = 76 - 38x + 51 + 6x + 83
89x - 32 = 210 - 32x
89x + 32x = 210 + 32
121x = 242
x = 242 : 121
x = 2
Ответ:х=2
Рад был помочь!
96x - 96 - 7x + 64 = 76 - 38x + 51 + 6x + 83
89x - 32 = 210 - 32x
89x + 32x = 210 + 32
121x = 242
x = 242 : 121
x = 2
Ответ:х=2
Рад был помочь!
Похожие вопросы
Предмет: Алгебра,
автор: sokol170385
Предмет: Математика,
автор: nerminh1985
Предмет: Математика,
автор: braynka78
Предмет: Литература,
автор: taes
Предмет: Биология,
автор: KEKAH